Graph-based D2D communication resource allocation algorithm in full duplex network - Chunzi SHI; Qi ZHU (Dianxin kexue)
For full duplex cellular communication scenario,a resource allocation algorithm based on graph coloring was proposed in order to maximize the throughput of the system.Firstly,the Hungarian algorithm was used to pair the upstream cellular users with the downstream cellular users.The pair of cellular users simultaneously used a resource block for uplink and downlink communication; then,under the premise of guaranteeing the quality of service of cellular users,channels were assigned for D2D (device-to-device) users based on graph theory coloring theory.Simulation results show that the algorithm can improve the system throughput and obtain higher spectral efficiency.